Technology, Media Literacy, and the Human Subject : A Posthuman Approach. - Lewis, Richard S. (Cambridge, UK : Open Book Publishers, 2021)
What does it mean to be media literate in today's world? How are we transformed by the many media infrastructures around us? We are immersed in a world mediated by information and communication technologies (ICTs). From hardware like smartphones, smartwatches, and home assistants to software like Facebook, Instagram, Twitter, and Snapchat, our lives have become a complex, interconnected network of relations. Scholarship on media literacy has tended to focus on developing the skills to access, analyze, evaluate, and create media messages without considering or weighing the impact of the technological medium--how it enables and constrains both messages and media users. Additionally, there is often little attention paid to the broader context of interrelations which affect our engagement with media technologies.
Intro -- Acknowledgements -- 1. Introduction: Problematizing our Relations with Media Technologies -- Situating the Research -- Media Literacy -- The Non-neutrality of Technological Relations -- Which Human Subject? -- Situating Media Literacy with Intrasubjective Mediation -- Research Significance and Design -- The Layout of the Chapters -- Concluding Thoughts -- Part I: Situating the Interdisciplinary Concepts -- 2. Situating Media Literacy -- Communication Beyond the Transmission Model -- Media Literacy Overview -- Expanding Media Literacy -- Concluding Thoughts -- 3. Understanding the Medium Through the Technological Relation -- In Medias Res -- Postphenomenology and the Technological Relation -- Media Ecology -- Concluding Thoughts -- 4. The Posthuman: Situating the Subject in Human-Tech Relations -- Humanists and Transhumanists Debating Enhancement -- The Posthuman Subject -- Complexity: The Key to Understanding Human Becomings -- Part II: Developing a Posthuman Approach: A Framework and Instrument -- 5. Developing the Intrasubjective Mediating Framework -- Situating the Intrasubjective Mediating Framework -- Intrasubjective Mediation -- The Intrasubjective Mediating Framework -- Intrasubjective Mediation: A Dance of Complexity -- Concluding Thoughts -- 6. Developing an Instrument to Leverage the Framework -- Creating the Instrument -- Identifying the Multiplicity of Relations -- Generalizing the Framework and Instrument for Media Literacy -- Concluding Thoughts -- 7. Conclusion -- Summary of Main Findings -- Strengths and Weaknesses of the Study -- Recommendations -- Final Thoughts -- References -- List of Tables and Illustrations -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books